Synthesis and Chara cterization of Composite Nanomaterials for Photonic Application - Shoriya Aruni, Abdul Manaf; Anuj, Kumar; Sharma, K.V.; Zainab, Ngaini; Gurumurthy, Hegde (2014)
Here we presented composite nanomaterials especially for the photonic device applications. Presented nanoparticles were synthesized using agricultural waste (as precursor) which drastically reduces the production cost. In the same time it can utilizes the usa-qe of agricultural biomass and prevent the environmental impact to occur. The composite nanomaterial is synthesized using pyrolysis method and further been characterized using Fourier Transfbrm Infrared Spectroscopy (FffR). X-ray Diffraction (XRD), FESEM-EDX and Transmission Electron Microscopy (TEM). The XRD results revealed the presence of carbon and iron particles where it can be clearly stated in the FESEM-EDX results showed the high percentage of carbon and iron. Bcsides that, the FESEM and TEM images showed that the particles are existed in nano sizes.